Happy feet two [videorecording (DVD)] - Miller, George, 1945 March 3-; Pitt, Brad, 1963-; Wood, Elijah, 1981-; Azaria, Hank, 1964-; P!nk, 1979-; Damon, Matt; Vergara, Sofía, 1972-; Williams, Robin, 1951-2014; Common (Musician) (Warner Home Video, 2012)
Tap-dancing Mumble's son Erik struggles to find his identity in the Emperor Penguin world as the whole community is threatened by an enormous iceberg.